Taxonomic study of the genus Kodaianella Fennah (Hemiptera: Fulgoromorpha: Issidae) - Zhang, Zheng-Guang; Chen, Xiang-Sheng (Zootaxa, 2010)
The genus of Kodaianella Fennah, 1956 (Hemiptera: Fulgoromorpha: Issidae: Issini), containing three species: K. bicinctifrons Fennah, 1956 (Guizhou: Congjiang, Xishui, Yanhe; Sichuan: Kangding), K. macheta sp. nov. (Guizhou: Guiyang; Henan: Huixian) and K. longispina sp. nov. (Yunnan: Dali, Baoshan), is here studied. All species are restricted to China. The generic characteristics are redefined. The main morphological characters and male genitalia of the three species are described, or redescribed, and illustrated. A key to species in the genus is provided.